Structural similitudes of stiffened cylinders. (March 2019) - Petrone, G; Manfredonia, M; De Rosa, S; Franco, F
Similarity theory is a branch of engineering science that deals with establishing conditions of similarity among phenomena and is applied to various fields, such as structural engineering problems, vibration and impact. Tests and numerical simulation of scaled models are still a valuable design tool, whose purpose is to accurately predict the behaviour of large or small prototypes through scaling laws applied to the experimental and numerical results. The aim of this paper is to predict the behaviour of the complete and incomplete similarity of stiffened cylinders by applying distorted scaling laws of the models in similitude. The investigation is performed using models based on the finite element method within commercial software. Two classes of cylinders scaled, with different laws, and, hence, reproducing replicas (exact similitude) and avatars (distorted similitude) are investigated.